A pilot investigation of the impact of acute mental and physical fatigue exposure on inflammatory cytokines and state fatigue level in breast cancer survivors - Ali A. Weinstein; Krish Seth; Shana Gordy; Kashaf Jabbar; Nylab Noori; Aybike Birerdinc; Ancha Baranova; Patrice Winter; Lynn H. Gerber (BMC Women's Health)
Abstract Background This study aims to analyze the changes in inflammatory cytokines and state fatigue after exposure to a mental or physical fatiguing activity in breast cancer survivors (BCS). Methods A total of 46 BCS women (age: 58.9 ± 9.1) were recruited for this study and randomly assigned to one of three groups: exposure to physical fatigue (n = 16), mental fatigue (n = 15), or control (n = 15). Participants exposed to physical fatigue performed a 6-minute walk/run test. Participants exposed to mental fatigue performed a version of a dual 2-back task on a computer. Participants in the control group watched a video for 6 min. Clinically significant fatigue was defined by the FACIT-F. Analytes in serum were profiled using the Bio-Plex 200 Suspension Array System, specifically IL-1β, IL-4, IL-5, IL-6, IL-8, IL-10, eotaxin, TNF-α, TGF-β1, and VEGF. Results Changes in inflammatory factors in response to the assigned fatigue-inducing tasks were mainly not statistically significant. The presence of clinically significant fatigue reported at baseline was, however, related to reactions to fatigue-inducing stimuli. Levels of TGF-β and eotaxin were consistently altered in reactions to fatigue-inducing tasks, particularly in those with clinical fatigue. Conclusions Clinically significant fatigue is related to increased inflammatory reactions to mentally or physically fatiguing tasks, highlighting the consistent impact that fatigue has across various challenges of daily activities. Acute fatigue challenges, the kind that BCS would be exposed to in everyday circumstances, does increase inflammatory responses, and those with clinically significant levels of fatigue at baseline are more likely to show these effects.